Knowledge and perceptions of patients with type 2 diabetes mellitus towards cardiovascular disease prevention: A review - Elnaem, Mohamed Hassan Abdelaziz; Jamal, Muhammad Hazim; Syed, Nabeel Kashan (2019)
Introduction: Patients with type 2 diabetes mellitus (T2DM) are at significantly higher risk of developing Cardiovascular disease (CVD). There is a lack of literature that describes and summarise T2DM patients’ knowledge and perception of CVD prevention. Objectives: To describe the extent of knowledge and perceptions of illness among T2DM patients concerning the current CVD preventive approaches. Methods: We adopted the methodology of systematic scoping review to guide in selecting the included articles, extracting and charting the results. We have retrieved the included studies from three scientific databases; Google Scholar, Science Direct and PubMed. A multistage screening process was followed. It considers relevancy, publication year (2009-2018), English language, and article type (original research involving T2DM patients). We formulated research questions focused on the assessment of levels of knowledge and perceptions of the illness relevant to CVD prevention. Results: A total of 16 studies were included. The findings showed variation in terms of T2DM patients’ knowledge and perceptions of individual CVD risk factors. The patients tended to overemphasize the role of lab tests in assessing CVD risks. It seems that the need for multifactorial risk assessments was overlooked. There were relatively negative perceptions of the benefits of CVD preventive medication therapies. The majority of the studies highlighted knowledge deficits. The patients’ perceptions were linked to their degree of adherence to lifestyle and pharmacotherapy recommendations. Conclusion: This work underpinned the prevalence of low levels of knowledge as well as negative perceptions towards T2DM illness, and its recommended CVD prevention measures. Therefore, customized initiatives and educational interventions for T2DM patients, concerning CVD preventive measures are probably needed and are strongly recommended.